PUBLIC TEACHER RECRUITMENT AND SELECTION IN INDONESIA: A LEGAL PERSPECTIVE - Ryan Saputra Alam,; Hurian Hurian Kamela (Scientia Business Law Review (SBLR), 2022)
The existence of Law No. 14 of 2005 and some thoughts that take is-sue with the low quality of teachers, one of the causes of which cannot be separated from the impact of the recruitment process and inadequate selection. It is necessary and urgent to conduct normative juridical studies to construct how the process of recruitment and selection of state teachers in Indonesia so that recruitment reconstruction and selection of ideal state teachers are produced in Indonesia. Two conclusions were made based on the knife analysis in the form of agency theory that emphasizes the contractual relationship between the principal and the agent that must reflect the efficient organization. First, the recruitment and selection of prospective state teachers have only been carried out en masse and almost simultaneously. The selection test is carried out by working on multiple-choice questions in which various types of questions are widely sold and can be learned or learned, even traced patterns of the problem. Thus, the correct answer to a question does not correlate with the ability of prospective teachers to carry out their duties and responsibilities later as a teacher who is loved and respected by students and colleagues. Second, it is necessary to update the rules related to the recruitment process and selection of prospective state teachers, including maximizing information technology in knowing the behavior of future teachers in using social media and so on.